Kesiapan Guru Dalam Penerapan Kurikulum Merdeka Belajar Pada Mata Pelajaran Bahasa Arab - Zumrotus Sangadah; Alfan Nurngain (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
This research discusses the readiness for implementing the "Merdeka Belajar" Curriculum in Arabic Language Education at the level of Madrasah Ibtidaiyah. The "Merdeka Belajar" Curriculum is an initiative by the Indonesian government to improve the quality of education and produce excellent human resources. Teachers is a key role in the success of curriculum implementation, but there are still challenges in understanding and effectively applying the "Merdeka Belajar" Curriculum. The research methodology used is qualitative descriptive, with data collected through interviews with teachers and literature review. The results show that Madrasah Ibtidaiyah has two options for curriculum implementation: using the 2013 Curriculum with some principles of the "Merdeka Belajar" Curriculum, or fully adopting the "Merdeka Belajar" Curriculum with graduation competency standards and learning achievements. Challenges faced by teachers in implementing the "Merdeka Belajar" Curriculum include limited understanding, lack of educational resources, and insufficient support from parents. Special seminars for educators to understand and apply the "Merdeka Belajar" Curriculum are needed. In conclusion, the implementation of the "Merdeka Belajar" Curriculum in Madrasah Ibtidaiyah aligns with the policies set by Kemendikbudristek, with adaptations to meet the specific needs of each Madrasah.